Herbicide dose-response thresholds in sands to assess the risk of non-target damage to winter grain crops - Win Win Pyone; Richard W. Bell; Michael T. Rose; Gavan S. McGrath (PLoS ONE, 2025)
Herbicide residues in soil from previous crops or from pre-emergent treatments can have unintended toxicity on the next crop. Despite this there is limited published information on toxicity thresholds for many crops or herbicides. This study aimed to quantify shoot and root responses of six common winter grains crops (canola, chickpea, fieldpea, lentil, lupin and wheat) to increasing concentration of four common herbicides (clopyralid, pyroxasulfone, propyzamide and trifluralin) in soil. Lentil emergence was highly sensitive to clopyralid (29 μg kg-1 for a 50% reduction, ED50) while wheat emergence was sensitive to propyzamide and trifluralin, with complete inhibition at 100 μg kg-1 and 375 μg kg-1, respectively. Shoot and root parameters of the legumes, except lupin, were significantly reduced by clopyralid, with ED50 values ranging between 3−27 μg kg-1. Canola was sensitive to pyroxasulfone, with shoot and root biomass ED50 at 21 and 8 μg kg-1, respectively. Pyroxasulfone also severely reduced root length of all tested crops (ED50 values 6−53 μg kg-1). Root and shoot growth in wheat was most susceptible to propyzamide followed by trifluralin. This study found that one or more herbicides had the potential to cause significant phytotoxic effects in all crops at concentrations below recommended application rates and below those detected in a recent field survey of pre-sowing herbicide residues in field soils around Australia. These results suggest the risk of early crop damage residual herbicides in very light-textured soils. More effort is now required to determine potential effects on different soil types and crop yields, to enable better spatial and economic risk assessment.